Dust emission from unpaved roads in Luleå, Sweden - Jia, Qi; Al-Ansari, Nadhir; Knutsson, Sven (Luleå tekniska universitet, Geoteknologi, 2013)
The dust emission from unpaved roads, if not controlled, can cause enormous problems. Though a few real-world measurements of road dust have been done by automated samplers in Sweden, measurement by BSNE (Big Spring Number Eight) and the estimation of total dust generation from vehicle driving is rare. This study measured and analyzed dust emission by BSNE at two unpaved roads in Luleå, Sweden, at the driving speed of 20, 30, 40, and 50 km/h different heights. Even though US EPA excluded vehicle speed as a parameter in estimating dust emission factors for unpaved roads, this study confirmed a strong dependence of dust emission on vehicle speed. This is in agreement with several recent studies which concluded dust emission increases with driving speed exponentially or linearly, however the power law is the best description for the data from this study. The comparison with estimated dust emission by US EPA’s equation showed the equation underestimates the dust emission more than 50 percent when vehicle speed and silt content is higher than 25.40km/h and 2.17 percent respectively. There might be some interrelationship between driving speed and silt content in road surface.Earlier researchers have reported increased dust emission with increasing silt content and this is confirmed by this study. Validerad; 2013; 20130212 (nadhir)